Fitrah-Based Education: A Holistic Model for Realizing the Rahmatan Lil'alamin Personality - Mardalena; Hendra Harmi; Dewi Purnama Sari (Newinera Publisher, 2026)
This research investigates and develops the Fitrah Based Education model to develop the Rahmatan Lil’alamin personality through a holistic single case study at SALIM School. This study responds to the demand for translating Islamic philosophical ideas of fitrah into educational components that link spiritual cultivation, talent cultivation, environmental responsibility, interaction adab and parental involvement. The data was gathered through participant observation, semi structured interviews, document study, and focus group discussion with students, facilitators, parents and school administration. The study suggests that the MPF RL model is built based on five interrelated components; the Tauhidic Curriculum, the Talent Civilization Project, the School of Life, the Interaction Adab, and the Parent Sessions. These components form an integrated educational ecosystem where students are guided to develop knowledge by means of Tafakkur fil Kawn, apply their talent to give benefits to the society through Talent to Mission, enhance their ecological responsibility through nature based education, practice peaceful relations through Interaction Adab, and sustain fitrah development through school home cooperation. The research concludes that the MPF RL model offers a contextual and empirical approach to operationalise Fitrah Based Education into educational practices. While the findings are only based on one case, they provide useful insights for Islamic educational institutions to produce students who are moral, life skilled, socially useful, ecological, and in line with the Rahmatan Lil’alamin paradigm.